Perbedaan Love Styles berdasarkan Jenis Kelamin pada Emerging Adult di Kota Padang - Jasmine, Putri; Rahmi, Iftita (Lembaga Yasin AlSys, 2025)
This study is motivated by the variations in expressions of love across individuals, influenced by culture, environment, and upbringing. In Minangkabau society, which adheres to a matrilineal kinship system, differing social roles and values between men and women may influence love styles. The objective of this research is to examine gender-based differences in love styles among Minangkabau emerging adults in Padang City. A comparative quantitative approach was employed with a sample of 400 Minangkabau emerging adults (200 males and 200 females), selected through purposive sampling. Data were collected using a love styles scale based on John Lee’s (1973) theory, with a reliability coefficient of 0.924. The questionnaire was distributed online, and data were analyzed using the Mann-Whitney test due to non-normal distribution. The results reveal significant gender differences in the love styles of eros, ludus, storge, pragma, and agape, while no significant difference was found for mania. The study concludes that gender influences variations in love styles among Minangkabau emerging adults, reflecting a cultural construction in which women are ascribed more dominant interpersonal roles. The findings contribute to cross-cultural psychology literature on love and provide a foundation for developing culturally and gender-sensitive psychological interventions.